HUBUNGAN PENGETAHUAN TENTANG RISIKO ABORSI DENGAN SIKAP REMAJA PUTRI TERHADAP ABORSI DI SMP WILAYAH BANGUNTAPAN BANTUL YOGYAKARTA - , Suesti, S.Si.T.; , Prof. dr. Djauhar I., SpA(K)., MPH., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background. Abortion is deliver of conception before viable. Risk of abortion such as: bleeding, infection, infertility, placenta in situ, mortality pregnancy. Abortion was done an ancient time, according data of WHO(World Organisation Health) 2/3 from 75 million unwanted pregnancy will be end with unsafe abortion about 20%. This way have contribute about 13% to the mother death in the world. Objective : The aim of the study is to explore the relationship between knowledge about the risk of abortion and adolescent attitude to abortion. Method: This is observational study with a cross sectional design using quantitative and qualitative approaches. Qualitatif data are collected by indepth interview. The subjects of the reseatch are 107 student of SMP Muhammadiyah I Banguntapan Bantul. Using sistematic random sampling. Result: The prevalece of adolescent with of Higher knowledge abortion risk than that with positive attitude. Using multi variable analysis, knowledge abortion risk related to adolescent positive attitude as abaut 2,56 times compare with low knowledge (RP=2,56